2011
DOI: 10.1016/j.neuron.2011.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Control of Neuronal Morphology by the Atypical Cadherin Fat3

Abstract: Neurons receive signals through dendrites that vary widely in number and organization, ranging from one primary dendrite to multiple complex dendritic trees. For example, retinal amacrine cells (ACs) project primary dendrites into a discrete synaptic layer called the inner plexiform layer (IPL) and only rarely extend processes into other retinal layers. Here, we show that the atypical cadherin Fat3 ensures that ACs develop this unipolar morphology. AC precursors are initially multipolar, but lose neurites as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(135 citation statements)
references
References 60 publications
8
122
0
Order By: Relevance
“…Since Fat3 is localized to processes in the IPL (Deans et al, 2011), we hypothesized that Fat3 propagates an overall change in cytoskeletal organization, echoing the effects of other Fat-related proteins on tissue polarity. In support of this idea, phalloidin staining revealed that F-actin was strongly enriched in the IPL of control retinas at postnatal day (P)11 (Fig.…”
Section: Fat3 Is Required For Directed Migration Of Amacrine Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Fat3 is localized to processes in the IPL (Deans et al, 2011), we hypothesized that Fat3 propagates an overall change in cytoskeletal organization, echoing the effects of other Fat-related proteins on tissue polarity. In support of this idea, phalloidin staining revealed that F-actin was strongly enriched in the IPL of control retinas at postnatal day (P)11 (Fig.…”
Section: Fat3 Is Required For Directed Migration Of Amacrine Cellsmentioning
confidence: 99%
“…1D). Fat3 can be detected in the IPL as soon as it forms (Deans et al, 2011), raising the possibility that this defect in mature amacrine cell morphology reflects an earlier role for Fat3 in the control of the cytoskeleton. Developing amacrine cells undergo rapid and transient changes in cytoskeletal organization that manifest as changes in cell shape.…”
Section: Fat3 Is Required For Directed Migration Of Amacrine Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…-/-mutants have altered dendritic morphology (Deans et al, 2011). Fat1 is proposed to control actin dynamics through interactions with Ena/Vasp proteins (Moeller et al, 2004;Tanoue and Takeichi, 2004).…”
Section: And Retinal Cells In Fat3mentioning
confidence: 99%
“…fat1 mutant mice die soon after birth and do not form proper glomerular slit junctions in kidneys (Ciani et al, 2003). In the developing retina, interneurons called amacrine cells lose their normal unipolar morphology in fat3 mutant animals, and instead acquire multipolar morphology (Deans et al, 2011). fat3 genetically interacts with the vertebrate fj ortholog fjx1 in regulating this process.…”
Section: 1 Vertebrate Ftmentioning
confidence: 99%